2005
DOI: 10.1002/adsc.200505012
|View full text |Cite
|
Sign up to set email alerts
|

The Substrate Spectrum of Mandelate Racemase: Minimum Structural Requirements for Substrates and Substrate Model

Abstract: Mandelate racemase (EC 5.1.2.2) is one of the few biochemically well-characterized racemases. The remarkable stability of this cofactor-independent enzyme and its broad substrate tolerance make it an ideal candidate for the racemization of non-natural a-hydroxycarboxylic acids under physiological reaction conditions to be applied in deracemization protocols in connection with a kinetic resolution step. This review summarizes all aspects of mandelate racemase relevant for the application of this enzyme in prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 50 publications
1
34
0
2
Order By: Relevance
“…[3] We have recently shown that mandelate racemase [EC 5.1.2.2] from Pseudomonas putida ATCC 12633 is an excellent catalyst for the isomerization of a wide spectrum of b,g-unsaturated a-hydroxycarboxylic acids. [4] However, saturated (aliphatic) analogues were not accepted at all. This limitation was successfully overcome by the use of whole resting cells of Lactobacillus spp., which allowed the clean racemization of a wide range of aliphatic and aryl-aliphatic a-hydroxycarboxylic acids.…”
mentioning
confidence: 99%
“…[3] We have recently shown that mandelate racemase [EC 5.1.2.2] from Pseudomonas putida ATCC 12633 is an excellent catalyst for the isomerization of a wide spectrum of b,g-unsaturated a-hydroxycarboxylic acids. [4] However, saturated (aliphatic) analogues were not accepted at all. This limitation was successfully overcome by the use of whole resting cells of Lactobacillus spp., which allowed the clean racemization of a wide range of aliphatic and aryl-aliphatic a-hydroxycarboxylic acids.…”
mentioning
confidence: 99%
“…[311] In Bezugnehmend auf ein oben bereits ausführlich diskutiertes Beispiel werden in Lit. [314] interessante Fortschritte bei der Entwicklung einer effizienten Mandelatracemase vorgestellt. In Lit.…”
Section: Verfahrenskonzepte Unter Berücksichtigung Der Racemisierungunclassified
“…[5] We have recently shown that mandelate racemase [EC 5.1.2.2] from Pseudomonas putida ATCC 12633 is an excellent biocatalyst for the racemization of a wide spectrum of β,γ-unsaturated α-hydroxycarboxylic acids. [6] The substrate spectrum of mandelate racemase has been found to be remarkably wide and encompasses various types of β,γ-unsaturated α-hydroxycarboxylic acids, such as substituted (hetero)aryl mandelic acid [7] (or amide) [8] analogues and even cyclic and open-chain 2-hydroxy-3-butenoic acid derivatives. However, aliphatic and aryl-aliphatic α-hydroxycarboxylic acids, which are unable to stabilize the α-carbanion intermediate formed during enzymatic racemization, turned out to be non-substrates.…”
Section: Introductionmentioning
confidence: 99%
“…However, aliphatic and aryl-aliphatic α-hydroxycarboxylic acids, which are unable to stabilize the α-carbanion intermediate formed during enzymatic racemization, turned out to be non-substrates. [6] In order to circumvent this limitation of mandelate racemase regarding its inability to interconvert the enantiomers of aliphatic and aryl-aliphatic α-hydroxycarboxylic acids, a matching α-hydroxyacid racemase activity was sought. Based on early reports on the lactate racemase activity of halophilic Archaea, anaerobic rumen bacteria and Lactobacillus spp., a screening recently provided a set of lactic acid bacteria that are able to racemize a broad spectrum of aliphatic and aryl-aliphatic α-hydroxycarboxylic acids at fair rates.…”
Section: Introductionmentioning
confidence: 99%